A systematic review of education programmes to prevent concussion in rugby union - Fraas, M. R.; Burchiel, J. (European Journal of Sport Science, 2016)
Background: There is a high incidence of concussion sustained by athletes participating in rugby union, many of which go unreported. A lack of sufficient knowledge about concussion injuries may explain athletes` failure to report. Several rugby union-playing countries have developed injury education and prevention programmes to address this issue. Objective: The aim of the current review was to systematically assess the content and level of evidence on concussion education/prevention programmes in rugby union and to make recommendations for the quality, strength, and consistency of this evidence. Methods: We searched PubMed, PsycInfo, MEDLINE, SPORTDiscuss, Webofscience, and conducted a manual search for articles. Results: Ten articles were included for review. Of these, six focused on the BokSmart injury prevention programme in South Africa, two focused on the RugbySmart injury prevention programme in New Zealand, one was an analysis of prevention programmes, and one was a systematic review of rugby injury prevention strategies. Conclusions: Despite the initiative to develop concussion education and prevention programmes, there is little evidence to support the effectiveness of such programmes. There is evidence to support education of coaches and referees. In addition, there is scant evidence to suggest that education and rule changes may have the benefit of changing athlete behaviours resulting in a reduction in catastrophic injury.